Case report of novel DYRK1A mutations in 2 individuals with syndromic intellectual disability and a review of the literature. Issue 1 (December 2016) - Luco, Stephanie; Pohl, Daniela; Sell, Erick; Wagner, Justin; Dyment, David; Daoud, Hussein
Abstract Background Chromosomal deletions encompassingDYRK1A have been associated with intellectual disability for several years. More recently, point mutations inDYRK1A have been shown to be responsible for a recognizable syndrome characterized by microcephaly, developmental delay and intellectual disability (ID) as well as characteristic facial features. Here we present 2 individuals with novel mutations inDYRK1A, and a review of the cases reported to date. Case presentation Both individuals presented with the well-known characteristic features, as well as rarer anomalies seen in a minority of patients. Patient 1 presented shortly after birth with an enlarged cisterna magna, distal contractures, and distinctive facies that included bitemporal narrowing and deep set eyes. Ade novo splice site mutation inDYRK1A [c.951 + 4_951 + 7delAGTA; p.Val222Aspfs*22] was identified by next generation sequencing. Patient 2 presented at 7 months of age with microcephaly and dysmorphic features. She went several years without a diagnosis until ade novo DYRK1A nonsense mutation [c.787C>T; p.(Arg263*)] was identified at age 12. These individuals, and the 52 cases reviewed from the literature, show the characteristic features of theDYRK1A -related syndrome including global developmental delay, ID, microcephaly, feeding difficulties, and the facial gestalt. Other common findings include seizures, vision defects, brain abnormalities and skeletal abnormalities of the hands and feet. Less common features include optic nerve defects, contractures, ataxia, and cardiac anomalies. Conclusion DYRK1A testing should be considered in individuals with the facial features, intellectual disability and post-natal microcephaly. Once diagnosed withDYRK1A -related intellectual disability, a cardiac and ophthalmologic assessment would be recommended as would routine surveillance by a pediatrician for psychomotor development, growth, and feeding.